Peircean Perspectives on the Global Climate Change Controversy - Baker, Victor (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2021)
The global climate change controversy is arguably the most important problem currently facing humankind. It involves seemingly insurmountable, conflicting issues of economics, science, politics, and philosophy. This essay suggests that, on the pathway to modernity, a kind of “wrong turn” was taken in these disciplines, involving problematic presumptions about phenomenology, logic, and metaphysics. A possible correction for current disfunctions, notably in the relation of economics to the physical sciences and political action, may found in the semiotic and pragmatist perspectives of the scientist/logician/philosopher Charles Sanders Peirce (1839-1914).